2012
DOI: 10.1371/journal.pone.0044471
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Binary Interaction Mapping of SH2 Domains via Fluorescence Polarization Reveals Novel Functional Diversification of ErbB Receptors

Abstract: First-generation interaction maps of Src homology 2 (SH2) domains with receptor tyrosine kinase (RTK) phosphosites have previously been generated using protein microarray (PM) technologies. Here, we developed a large-scale fluorescence polarization (FP) methodology that was able to characterize interactions between SH2 domains and ErbB receptor phosphosites with higher fidelity and sensitivity than was previously achieved with PMs. We used the FP assay to query the interaction of synthetic phosphopeptides corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 55 publications
2
95
0
Order By: Relevance
“…Therefore, best-fit consensus motifs are definitely not required for SH2 domain containing proteins to function in a physiological context. In our study [1], we empirically demonstrated that EGFR does not contain a single high-affinity recruitment site for Src family kinase SH2 domains. The highest affinity EGFR recruitment site had a dissociation constant of approximately 2 µM, much less than the 3 nM dissociation constants originally described for the pYEEI consensus peptide [20].…”
Section: Editorialmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, best-fit consensus motifs are definitely not required for SH2 domain containing proteins to function in a physiological context. In our study [1], we empirically demonstrated that EGFR does not contain a single high-affinity recruitment site for Src family kinase SH2 domains. The highest affinity EGFR recruitment site had a dissociation constant of approximately 2 µM, much less than the 3 nM dissociation constants originally described for the pYEEI consensus peptide [20].…”
Section: Editorialmentioning
confidence: 71%
“…We recently described one of the most comprehensive and quantitative assessments of human ErbB receptor recruitment potential for SH2 domains to date using a high-throughput fluorescence polarization methodology [1]. This study uncovered 1405 unique interactions, 83% of which had not been previously described and the majority of which were of low affinity relative to previously described best-fit interaction motifs for SH2 domains.…”
Section: Editorialmentioning
confidence: 98%
“…To reduce the number of potential binding proteins, we relied on two sets of experimental data. First, we required that binding proteins have less than a 3 mM K d to any EGFR tyrosine phosphorylation site [13]. Second, we required that binding proteins have detectable concentrations as measured in NIH3T3 cells [16].…”
Section: Choosing Tyrosine Phosphorylation Sites Binders and Rate Comentioning
confidence: 99%
“…On the epidermal growth factor receptor (EGFR), phosphorylation of Y1068 is correlated with longer survival in non-small cell lung cancer patients, whereas phosphorylation of Y1173 is correlated with shorter survival [12]. There are multiple proteins, such as Grb2, PI3K, SHP2, PLCg1, RasA1 ( p120RasGAP) and Shc1, which bind to these and the other approximately 10 tyrosine phosphorylation sites on EGFR in both unique and overlapping manners with varying affinities [13]. The relative recruitment levels of these various proteins determine the strength of downstream signalling to pathways such as Akt, ERK or PKC, which subsequently dictate biological responses such as proliferation, migration, differentiation or apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation